ANALYSIS OF METAPHORICAL MEANINGFUL UNITS IN A LITERARY TEXT (On the example of the works of Nazar Eshonkul) - Muslimjon Nasirov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, the phenomenon of association, which is considered the most important factor in the formation of metaphorical content microtexts, is analyzed through examples from the works of Nazar Eshankul.